Fluvoxamine affects sildenafil kinetics and dynamics - Hesse, Christiane; Siedler, Heike; Burhenne, Jürgen; Riedel, Klaus-Dieter; Haefeli, Walter E. (Journal of clinical psychopharmacology, 2005)
Sildenafil used as oral drug treatment for erectile dysfunction is predominantly metabolized by the cytochrome P450 isozyme 3A4. The antidepressant fluvoxamine is an inhibitor of cytochrome P450 3A4. In a randomized, double-blind, placebo-controlled, crossover study, we evaluated the effects of fluvoxamine dosed to steady state on the pharmacokinetics and pharmacodynamics of sildenafil. Twelve healthy men received oral fluvoxamine or placebo for 10 days (50 mg every day on days 1-3; 100 mg every day on days 4-10). On day 11, all participants received a single, oral, open-label dose of 50 mg sildenafil, and blood samples were collected for analysis of sildenafil plasma concentrations by liquid chromatography/mass spectrometry. Concurrently, the effect of sildenafil on venodilation induced by a constant dose of sodium nitroprusside was assessed using the dorsal hand vein compliance technique. Sildenafil was well tolerated in the presence of fluvoxamine. During fluvoxamine, sildenafil exposure (area under the curve) significantly increased by 40% (P < 0.001), and its half-life increased by 19% (P = 0.034). Concurrently, sodium nitroprusside-induced venodilation was significantly augmented by 59% during fluvoxamine compared to placebo (P = 0.012). In conclusion, sildenafil kinetics are mildly affected by fluvoxamine which translates into an increase in vascular sildenafil effects. Whereas the pharmacokinetic changes do not suggest a large clinically relevant interaction, it may be prudent to consider a starting dose of 25 mg in patients concurrently treated with fluvoxamine.
Gesehen am 17.05.2021